Students' leisure weekend activities during movement control order: UiTM Pahang sharing experience / Syafiza Saila Samsudin ... [et al.] - Samsudin, Syafiza Saila; Mohamad Adnan, Noor Izyan; Nik Badrul Alam, Nik Muhammad Farhan Hakim; Mohamed, Siti Rosiah; Ismail, Nazihah (2021)
A movement control order implemented by Malaysia's government due to the COVID-19 pandemic has strictly controlled the education system, where virtual classes have taken over the physical classes. This study aims to describe the students' leisure weekend activities during movement control order in Universiti Teknologi MARA Pahang. A simple random sampling technique was conducted by distributing online survey questionnaires to a sample of 213 students. A descriptive statistics, and Chi-Square and Fisher Exact test were used in data exploration and association determination between students' activities and demographic characteristics. Results found that majority of the students did not make a weekend to-do list and slept more than four hours. Most of the females, 53% enjoyed their weekend, but 51% of males did not. Many students spent more than four hours on revision, 25% and social media, 27%. Most of them spent less than one hour on family, 31% and reading, 53% activities. The study concludes that there are seven activities are influenced by gender, four activities are influenced by programs, while two activities are influenced by their current semester.